Cybernetic approach to the construction of the intensification system for the study process in high schools (the aspect of structuring) - Ризун, Нина Олеговна (Eastern-European Journal of Enterprise Technologies, 2011)
The integral algorithm of formation of scientific and innovative multilevel complex of study process with the use of information technologies is suggested, the decomposed hierarchy structure of subsystems being developed